2017
DOI: 10.4186/ej.2017.21.4.139
|View full text |Cite
|
Sign up to set email alerts
|

Development of Thai Silk Fibroin/Hyaluronic Acid Microspheres and the Application on Controlled Release of Curcumin

Abstract: Abstract. The aim of this study was to develop microspheres from Thai silk fibroin (SF) blended with hyaluronic acid (HA) for controlled release application. HA was introduced to blend with SF to enhance properties of the microspheres. The SF-based microspheres could be prepared by water in oil emulsion and glutaraldehyde crosslinking technique. The obtained microspheres contained 71-91% SF and 9-29% HA. The microspheres having higher SF content showed more stability and slower degradation rate. Then, to prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…aimed to prepare microspheres from Thai silkin (SF) blended with hyaluronic acid (HA), and the results showed that microspheres with a higher SF content had higher stability and slower degradation rates. In addition, in order to demonstrate the potential of use of adsorbed curcumin in the microspheres, it was finally shown that all SFHA microspheres were released drugs controlled manner [ 182 ].…”
Section: Microsphere Processing Materialsmentioning
confidence: 99%
“…aimed to prepare microspheres from Thai silkin (SF) blended with hyaluronic acid (HA), and the results showed that microspheres with a higher SF content had higher stability and slower degradation rates. In addition, in order to demonstrate the potential of use of adsorbed curcumin in the microspheres, it was finally shown that all SFHA microspheres were released drugs controlled manner [ 182 ].…”
Section: Microsphere Processing Materialsmentioning
confidence: 99%
“…Combining the properties of natural protein and polysaccharides can be a promising strategy to obtain bioactive materials with a controlled structure in the biomedical field [ 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ]. In silk fibroin/hyaluronic acid scaffolds, increasing hyaluronic acid content significantly enhanced the water binding capacity and flexibility [ 140 ].…”
Section: Blendingmentioning
confidence: 99%
“…In in vivo studies, the hydrogels based on silk fibroin/hyaluronic acid blends presented good histocompatibility and promoted vascular-like tissue regeneration when were implanted subcutaneously in Sprague Dawley rats [ 143 ]. Regarding microspheres to the application on controlled release, the microspheres having higher silk fibroin content showed slower degradation rate and more stability [ 144 ]. Curcumin, used as an antioxidant with anticancer activity, was adsorbed in the microspheres and all microspheres released curcumin in a controllable manner.…”
Section: Blendingmentioning
confidence: 99%
See 1 more Smart Citation